Content of modern constitutions: trends in the post-Soviet space - Maslovskaya, Tatiana S. (Journal of the Belarusian State University. Law, 2025)
The article examines constitutional innovations that testify to the substantive expansion of constituent acts. New legal structures are considered, including new objects of constitutional regulation. The analysis is based on the latest constitutional reforms carried out in some post-Soviet states (Azerbaijan, Armenia, Belarus, Kazakhstan, Kyrgyzstan, Uzbekistan). Attention is drawn to the strengthening of the value content of constitutions, the strengthening of moral principles, national and original features, as well as the expansion of provisions related to the development of scientific and technological progress.